Ebanga™: The most recent FDA-approved drug for treating Ebola - Taki, Elahe; Ghanavati, Roya; Navidifar, Tahereh; Dashtbin, Shirin; Heidary, Mohsen; Moghadamnia, Marjan (Frontiers in Pharmacology, 2023)
Ebolavirus (EBOV) is a virulent pathogen that causes Ebola virus disease (EVD), which is a life-threatening human condition with a fatality rate of up to 90%. Since the first outbreak in Africa in 1976, several outbreaks and epidemics of EBOV have occurred across the globe. While EVD is recognized as a serious threat to human health and outbreaks occur almost every year, the treatment options for the disease are limited. In designing therapeutic strategies against EBOV infection, viral structural proteins, such as glycoprotein (GP), could be an excellent target for neutralizing the virus. According to the latest research, GP-specific antibodies are the most efficient post-exposure treatments for EVD. Ansuvimab-zykl, i.e., mAb114 (Ebanga™), is a recent FDA-approved human immunoglobulin monoclonal antibody targeting EBOV GP. This review provides a brief overview of the pharmacological effects and safety profile of ansuvimab in clinical trials and provides insights into the precise mechanism of this new drug for treating EVD.